Hexaaluminate / oxide forming catalyst for N2O decomposition in nitric acid oxidation furnace and preparation method of hexaaluminate / oxide forming catalyst
By preparing hexaluminate/oxide molding catalyst and roasting in an N2O atmosphere, the problem of decomposing N2O in a nitric acid oxidation furnace is solved, and the nitric acid yield and catalyst stability are improved.
Patent Information
- Application Number
- CN202411720874.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
During the production of nitric acid in the ammonia contact oxidation process, it is difficult for the catalyst to stably decompose N2O under the high temperature and water vapor environment in the nitric acid oxidation furnace, and it has an impact on the yield of NO, resulting in a decrease in the yield of nitric acid.
A hexaluminate/oxide molding catalyst was used to prepare a catalyst with high specific surface area and high temperature stability through co-precipitation reaction, calcination and molding process, and further calcination was carried out in an N2O atmosphere to regulate the active components of the catalyst.
The performance of catalysts on N2O decomposition is significantly improved, the yield of NO is maintained, the yield of nitric acid in the nitric acid oxidation furnace is improved, and the high temperature stability of the catalyst is enhanced.
Smart Images

Figure SMS_1 
Figure HDA0005158005400000011 
Figure HDA0005158005400000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of producing nitric acid by ammonia contact oxidation method, and specifically relates to a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace and a preparation method thereof. Background Art
[0002] Nitric acid is an important raw material for chemical production. In industry, its downstream products cover many fields such as fertilizers, explosives, pesticides and dyes. In the current mainstream ammonia contact oxidation process for producing nitric acid, N2O and NO are produced. x Two pollutants. The ammonia contact oxidation process for producing nitric acid is carried out at a high temperature of 800-900°C, with metal platinum as a catalyst. NH3 reacts with O2 to produce a large amount of NO, which is further oxidized to produce NO2. NO2 eventually reacts with H2O in the absorption tower to produce nitric acid. However, it is worth noting that in this process, ammonia and oxygen may also undergo side reactions at the platinum mesh, thereby producing the byproduct greenhouse gas N2O. Since N2O cannot be absorbed by aqueous solutions, it will eventually be directly emitted into the atmosphere, where it will remain in nature for 70 to 100 years, and its greenhouse effect is 310 times that of CO2.
[0003] Patent CN111108063B elaborates in detail that in the field of nitric acid production process, according to the stage of nitric acid process, the reduction of N2O emission is divided into primary to four stages. Since N2O does not play a role in the formation of nitric acid, it can be removed in the early process steps. Measures to avoid the formation of N2O during ammonia oxidation are called primary emission reduction; the removal of N2O from the gas after ammonia oxidation and before the absorption stage is called secondary emission reduction; the reduction of N2O in the tail gas from the absorption stage upstream of the tail gas expander is called tertiary emission reduction. The reduction of N2O emission after expansion (i.e. downstream of the expander) is called quaternary emission reduction.
[0004] At present, there has been great progress in the research on various methods for reducing N2O emissions in the tail gas of nitric acid production. One of the more economical methods is to load a specific catalyst under the precious metal mesh of the nitric acid oxidation furnace, and directly treat it when N2O passes through the platinum mesh, that is, remove N2O from the gas after ammonia oxidation and before the absorption stage, thereby avoiding the addition of emission reduction devices, thereby reducing construction costs and operating costs. However, the reaction in the nitric acid oxidation furnace has a high space velocity, contains 17% water and 10% NO, and the temperature is as high as 800-900°C, which places extremely high requirements on the high-temperature stability of the catalyst. At the same time, the concentration of NO, the intermediate reaction product, will directly affect the output of nitric acid.
[0005] Patent CN102008954A discloses three preparation methods of hexaaluminate catalysts, namely, coprecipitation method, sol-gel method and reverse microemulsion method. Hexaaluminate has good thermal stability, strong sintering resistance, high mechanical strength and high thermal resistance. It can maintain a large specific surface area under high temperature conditions and has been widely used in the fields of methane carbon dioxide reforming, methane hydrogen production, methane catalytic combustion, etc.
[0006] Therefore, how to prepare an efficient hexaaluminate crystalline catalyst to directly purify and decompose N2O at a high temperature of 850°C in a nitric acid oxidation furnace without changing the production of NO has become an urgent problem to be solved. Summary of the invention
[0007] In view of the problems in the prior art, the present invention provides a hexaaluminate shaped catalyst for decomposing N2O in a nitric acid oxidation furnace and a preparation method thereof.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] The present invention provides a method for preparing a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace, comprising the following steps:
[0010] (1) preparing a nitrate solution with a pH of 1, adding a precipitant to the nitrate solution to obtain a coprecipitation reaction system, carrying out a coprecipitation reaction at 60 to 80° C. for 3 to 6 hours, washing with water, drying, and then calcining at 1100 to 1200° C. for 4 to 6 hours in a N2O atmosphere to obtain a hexaaluminate catalyst;
[0011] (2) stirring a hexaaluminate catalyst, an oxide and water at 60 to 90° C. for 4 to 6 hours, rotary evaporating, and then calcining at 850 to 950° C. for 4 to 6 hours to obtain a hexaaluminate / oxide catalyst;
[0012] (3) fully mixing the hexaaluminate / oxide catalyst, a binder, an extrusion aid, a peptizing agent and water to prepare a clay embryo, aging the clay embryo, extruding and molding it, drying it, and then calcining it at 850-950° C. for 4-6 hours to obtain a hexaaluminate / oxide molded catalyst;
[0013] The oxide is one or two of aluminum oxide, zirconium oxide and silicon oxide.
[0014] Preferably, the nitrate in step (1) consists of nitrate of alkaline earth metal or rare earth metal, nitrate of transition metal and aluminum nitrate in a molar ratio of 1:1:11.
[0015] More preferably, the alkaline earth metal nitrate is at least one of barium nitrate and magnesium nitrate, the rare earth metal nitrate is lanthanum nitrate, and the transition metal nitrate is at least one of copper nitrate, iron nitrate and cobalt nitrate.
[0016] Preferably, the precipitant in step (1) is a saturated ammonium carbonate solution, and the pH of the coprecipitation reaction system is 7 to 7.5.
[0017] More preferably, the drying conditions of the reactants in step (1) are: drying at 120° C. for 6 to 8 hours.
[0018] Preferably, the amount of the oxide added in step (2) is 3.5 to 4.5 times the weight of the hexaaluminate catalyst.
[0019] Preferably, the binder in step (3) is pseudo-boehmite, the extrusion aid is sesbania powder, and the peptizing agent is concentrated nitric acid.
[0020] Further preferably, in step (3), the mass ratio of the hexaaluminate / oxide catalyst, the binder, the extrusion aid and the peptizing agent is (40-70): (18-40): (4-10): (6-12).
[0021] Further preferably, the aging conditions in step (3) are: aging at room temperature, in a cool and dry condition.
[0022] Further preferably, the drying conditions of the catalyst in step (3) are: drying at 120° C. for 12 h.
[0023] Preferably, the calcination heating rate of step (1), step (2) and step (3) is 4°C / min.
[0024] The present invention also provides a hexaaluminate / oxide shaped catalyst prepared by the above preparation method.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The catalyst of the present invention disperses the hexaaluminate by loading it with oxides, greatly increasing its specific surface area, thereby enhancing the activity of the catalyst. Oxides have abundant acid sites, and when loaded, the hexaaluminate is easy to combine with the acid sites, while N2O is more likely to combine with the acid sites when in contact with the catalyst, which is conducive to the combination of N2O and the active component (hexaaluminate). Therefore, the performance of the catalyst of the present invention in catalyzing the decomposition of N2O is greatly improved.
[0027] (2) The catalyst of the present invention introduces N2O during calcination to regulate the crystal faces of the active component (hexaaluminate). After high temperature, the exposed crystal faces of the hexaaluminate crystal phase acquire the ability to easily combine with N2O, which enables the hexaaluminate to obtain a high active surface and improves the performance of the catalyst in catalyzing the decomposition of N2O.
[0028] (3) The catalyst of the present invention can effectively eliminate the diffusion resistance during the mixed reaction by doping transition metal elements such as Fe and Co, prevent the agglomeration of metal atoms in the catalyst, and make the active metals highly dispersed on the formed hexaaluminate crystal phase, which is beneficial to the formation of the hexaaluminate lattice and also enhances the high-temperature stability of the hexaaluminate crystal.
[0029] (4) The catalyst of the present invention can produce NO while catalytically decomposing N2O. The produced NO can be used as a raw material for subsequent nitric acid production. That is, when the catalyst of the present invention is used in a nitric acid oxidation furnace, the nitric acid output of the overall process can be increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 XRD patterns of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 3;
[0031] Figure 2 H2-TPR spectra of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 4. DETAILED DESCRIPTION
[0032] The method of the present invention is described in detail below with reference to specific examples.
[0033] Example 1
[0034] A method for preparing a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace comprises the following steps:
[0035] (1) According to the molar ratio of lanthanum nitrate, copper nitrate, iron nitrate and aluminum nitrate of 1:0.8:0.2:11, 8.66g of lanthanum nitrate hexahydrate, 3.87g of copper nitrate trihydrate, 1.62g of iron nitrate nonahydrate and 82.5g of aluminum nitrate nonahydrate were added to 60°C constant temperature deionized water, stirred evenly and the solution was adjusted to pH=1 with dilute nitric acid to obtain a nitrate mixed solution; a precipitant saturated ammonium carbonate solution was added to the nitrate mixed solution until the pH was 7, and the obtained solution was subjected to coprecipitation reaction at 60°C for 3h, the obtained reactant was washed with deionized water, filtered, and placed in an oven at 120°C for 8h; the obtained sample was ground into powder, spread in a crucible and placed on a tube furnace, and then calcined at 1200°C for 4h at a heating rate of 4°C / min in a N2O atmosphere to obtain LaCu 0.8 Fe 0.2 Al 11 O19 The hexaaluminate catalyst is 14.42 g, the theoretical yield is 16.04 g, and the yield is 89.9%.
[0036] (2) 14 g of hexaaluminate catalyst and 56 g of γ-Al2O3 oxide were added to an eggplant-shaped bottle, and then 100 mL of water was added and stirred at 80°C for 4 h. The obtained reactant was subjected to rotary evaporation. The sample on the wall of the eggplant-shaped bottle after the rotary evaporation was scraped off and ground into powder; the powder was spread flat in a crucible and placed in a muffle furnace, and then calcined at 900°C for 4 h at a heating rate of 4°C / min to obtain LaCu 0.8 Fe 0.2 Al 11 O 19 / Al2O3 hexaaluminate / oxide catalyst 68.9g.
[0037] (3) 65 g of hexaaluminate / oxide catalyst, 25 g of pseudo-boehmite and 8 g of sesbania powder were placed in a kneader and stirred until uniform, and then 10 g of concentrated nitric acid and 80 mL of deionized water were added and mixed to obtain a uniform mud embryo; the mud embryo was placed in a room temperature, cool and dry condition for aging, and then extruded by a double-screw extruder, and the formed catalyst was dried at 120°C for 12 h, and finally placed in a muffle furnace at a constant temperature of 800°C for 6 h at a heating rate of 4°C / min to obtain LaCu 0.8 Fe 0.2 Al 11 O 19 / Al2O3 hexaaluminate / oxide shaped catalyst.
[0038] Example 2
[0039] A method for preparing a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace comprises the following steps:
[0040] (1) According to the molar ratio of lanthanum nitrate, copper nitrate and aluminum nitrate of 1:1:11, 10.83 g of lanthanum nitrate hexahydrate, 6.04 g of copper nitrate trihydrate and 103.16 g of aluminum nitrate nonahydrate were added to 60°C constant temperature deionized water, stirred evenly and the solution was adjusted to pH=1 with dilute nitric acid to obtain a nitrate mixed solution; a precipitant saturated ammonium carbonate solution was added to the nitrate mixed solution until the pH was 7, and the obtained solution was subjected to a coprecipitation reaction at 60°C for 3 hours, the obtained reactant was washed with deionized water, filtered, and dried in an oven at 120°C for 8 hours; the obtained sample was ground into powder, spread in a crucible and placed on a tube furnace, and then calcined at 1200°C for 4 hours at a heating rate of 4°C / min in a N2O atmosphere to obtain LaCuAl 11 O 19The hexaaluminate catalyst is 18.57 g, the theoretical yield is 20.09 g, and the yield is 92.43%.
[0041] (2) 15 g of hexaaluminate catalyst and 60 g of oxide γ-Al2O3 were added to an eggplant-shaped bottle, and then 100 mL of water was added, and the mixture was stirred at 80°C for 4 h. The obtained reactant was subjected to rotary evaporation, and the sample on the wall of the eggplant-shaped bottle after the rotary evaporation was scraped off and ground into powder; the powder was spread evenly in a crucible and placed in a muffle furnace, and then calcined at 900°C for 4 h at a heating rate of 4°C / min to obtain LaCuAl 11 O 19 / Al2O3 hexaaluminate / oxide catalyst 72.9g.
[0042] (3) 70 g of hexaaluminate / oxide catalyst, 20 g of pseudo-boehmite and 8 g of sesbania powder were placed in a kneader and stirred until uniform, and then 10 g of concentrated nitric acid and 100 mL of deionized water were added to mix them thoroughly to obtain a uniform mud embryo; the mud embryo was placed in a room temperature, cool and dry condition for aging, and then extruded by a double-screw extruder, and the formed catalyst was dried at 120°C for 12 h, and finally placed in a muffle furnace at a constant temperature of 800°C for 6 h at a heating rate of 4°C / min to obtain LaCuAl 11 O 19 / Al2O3 hexaaluminate / oxide shaped catalyst.
[0043] Comparative Example 1
[0044] A method for preparing a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace comprises the following steps:
[0045] (1) According to the molar ratio of lanthanum nitrate, copper nitrate and aluminum nitrate of 1:1:11, 30.31 g of lanthanum nitrate hexahydrate, 16.91 g of copper nitrate trihydrate and 288.85 g of aluminum nitrate nonahydrate were added to 60°C constant temperature deionized water, stirred evenly and the solution was adjusted to pH=1 with dilute nitric acid to obtain a nitrate mixed solution; a precipitant saturated ammonium carbonate solution was added to the nitrate mixed solution until the pH was 7, and the obtained solution was subjected to a coprecipitation reaction at 60°C for 3 hours, the obtained reactant was washed with deionized water, filtered, and placed in an oven at 120°C for 8 hours; the obtained sample was ground into powder, spread flat in a crucible, placed in a muffle furnace, and calcined at 1200°C for 4 hours at a heating rate of 4°C / min to obtain LaCuAl 11 O 19 The hexaaluminate catalyst is 51.64 g, the theoretical yield is 56.24 g, and the yield is 91.82%.
[0046] (2) 50g LaCuAl 11 O19 The catalyst, 30 g of pseudo-boehmite and 6 g of sesbania powder were put into a kneader and stirred until uniform, and then 10 g of concentrated nitric acid and 60 mL of deionized water were added to mix them thoroughly to obtain a clay embryo with uniform texture; the clay embryo was placed under normal temperature, cool and dry conditions for aging, and then extruded by a double-screw extruder, and the formed catalyst was dried at 120 ° C for 12 h, and finally placed in a muffle furnace at a constant temperature of 800 ° C for 6 h at a heating rate of 4 ° C / min to obtain LaCuAl 11 O 19 Hexaaluminate shaped catalyst.
[0047] Comparative Example 2
[0048] A method for preparing a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace comprises the following steps:
[0049] (1) According to the molar ratio of lanthanum nitrate, copper nitrate and aluminum nitrate of 1:1:11, 30.31g of lanthanum nitrate hexahydrate, 16.91g of copper nitrate trihydrate and 288.85g of aluminum nitrate nonahydrate were added to 60°C constant temperature deionized water, stirred evenly and the solution was adjusted to pH=1 with dilute nitric acid to obtain a nitrate mixed solution; a precipitant saturated ammonium carbonate solution was added to the nitrate mixed solution until the pH was 7, and the obtained solution was subjected to coprecipitation reaction at 60°C for 3h, the obtained reactant was washed with deionized water, filtered and placed in an oven at 120°C for 8h; the obtained sample was ground into powder, spread in a crucible and placed on a tube furnace, and then calcined at 1200°C for 4h at a heating rate of 4°C / min in a N2O atmosphere to obtain LaCuAl 11 O 19 The hexaaluminate catalyst is 51.67 g, the theoretical yield is 56.24 g, and the yield is 91.88%.
[0050] (2) 50g LaCuAl 11 O 19 The catalyst, 30 g of pseudo-boehmite and 6 g of sesbania powder were put into a kneader and stirred until uniform, and then 10 g of concentrated nitric acid and 60 mL of deionized water were added to mix them thoroughly to obtain a uniform mud embryo; the mud embryo was placed under normal temperature, cool and dry conditions for aging, and then extruded using a double-screw extruder. The molded catalyst was dried at 120 ° C for 12 h, and finally placed in a muffle furnace at a constant temperature of 900 ° C for 6 h at a heating rate of 4 ° C / min to obtain LaCuAl 11 O 19 Hexaaluminate shaped catalyst.
[0051] Comparative Example 3
[0052] A method for preparing a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace comprises the following steps:
[0053] (1) According to the molar ratio of lanthanum nitrate, copper nitrate, cobalt nitrate and aluminum nitrate of 1:0.8:0.2:11, 38.97g of lanthanum nitrate hexahydrate, 17.40g of copper nitrate trihydrate, 5.24g of cobalt nitrate hexahydrate and 371.38g of aluminum nitrate nonahydrate were added to 60°C constant temperature deionized water, stirred evenly and the solution was adjusted to pH=1 with dilute nitric acid to obtain a nitrate mixed solution; a precipitant saturated ammonium carbonate solution was added to the nitrate mixed solution until the pH was 7, and the obtained solution was subjected to coprecipitation reaction at 60°C for 3h, the obtained reactant was washed with deionized water, filtered, and dried in an oven at 120°C for 8h; the obtained sample was ground into powder, spread flat in a crucible, placed in a muffle furnace, and calcined at 1200°C for 4h at a heating rate of 4°C / min to obtain LaCu 0.8 Co 0.2 Al 11 O 19 The hexaaluminate catalyst is 66.49 g, the theoretical yield is 73.15 g, and the yield is 90.9%.
[0054] (2) 65g LaCu 0.8 Co 0.2 Al 11 O 19 The catalyst, 25 g of pseudo-boehmite and 10 g of sesbania powder were put into a kneader and stirred until uniform, and then 12 g of concentrated nitric acid and 80 mL of deionized water were added to mix them thoroughly to obtain a uniform mud embryo; the mud embryo was placed under normal temperature, cool and dry conditions for aging, and then extruded using a double-screw extruder, and the formed catalyst was dried at 120 ° C for 12 h, and finally placed in a muffle furnace at a constant temperature of 800 ° C for 6 h at a heating rate of 4 ° C / min to obtain LaCu 0.8 Co 0.2 Al 11 O 19 Hexaaluminate shaped catalyst.
[0055] Comparative Example 4
[0056] A method for preparing a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace comprises the following steps:
[0057] (1) According to the molar ratio of lanthanum nitrate, copper nitrate and aluminum nitrate of 1:1:11, 10.83 g of lanthanum nitrate hexahydrate, 6.04 g of copper nitrate trihydrate and 103.16 g of aluminum nitrate nonahydrate were added to 60°C constant temperature deionized water, stirred evenly and the solution was adjusted to pH=1 with dilute nitric acid to obtain a nitrate mixed solution; a precipitant saturated ammonium carbonate solution was added to the nitrate mixed solution until the pH was 7, and the obtained solution was subjected to a coprecipitation reaction at 60°C for 3 hours, the obtained reactant was washed with deionized water, filtered, and placed in an oven at 120°C for 8 hours; the obtained sample was ground into powder, spread in a crucible, placed in a muffle furnace, and calcined at 1200°C for 4 hours at a heating rate of 4°C / min to obtain LaCuAl 11 O 19 The hexaaluminate catalyst is 18.57 g, the theoretical yield is 20.09 g, and the yield is 92.43%.
[0058] (2) 15 g of hexaaluminate catalyst and 60 g of oxide γ-Al2O3 were added to an eggplant-shaped bottle, and then 100 mL of water was added, and the mixture was stirred at 80°C for 4 h. The obtained reactant was subjected to rotary evaporation, and the sample on the wall of the eggplant-shaped bottle after the rotary evaporation was scraped off and ground into powder; the powder was spread evenly in a crucible and placed in a muffle furnace, and then calcined at 900°C for 4 h at a heating rate of 4°C / min to obtain LaCuAl 11 O 19 / Al2O3 hexaaluminate / oxide catalyst 72.9g.
[0059] (3) 70 g of hexaaluminate / oxide catalyst, 20 g of pseudo-boehmite and 8 g of sesbania powder were placed in a kneader and stirred until uniform, and then 10 g of concentrated nitric acid and 100 mL of deionized water were added to mix them thoroughly to obtain a uniform mud embryo; the mud embryo was placed in a room temperature, cool and dry condition for aging, and then extruded by a double-screw extruder, and the formed catalyst was dried at 120°C for 12 h, and finally placed in a muffle furnace at a constant temperature of 800°C for 6 h at a heating rate of 4°C / min to obtain LaCuAl 11 O 19 / Al2O3 hexaaluminate / oxide shaped catalyst.
[0060] Catalyst characterization tests:
[0061] 1. Specific surface area test
[0062] The specific surface area of the molded catalysts prepared in Example 1 and Comparative Examples 1 to 4 was tested, and the results are shown in Table 1.
[0063] Table 1 Catalyst specific surface area
[0064] serial number <![CDATA[Specific surface area [m 2 ·g -1 > Example 1 28.61 Example 2 24.58 Comparative Example 1 13.05 Comparative Example 2 14.86 Comparative Example 3 18.34 Comparative Example 4 23.17
[0065] It can be seen from Table 1 that after loading the oxide, the specific surface area of the catalyst increases significantly, thereby improving the catalyst activity.
[0066] 2. XRD test
[0067] The shaped catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 3 were subjected to XRD test. The results are as follows: Figure 1 As shown. Figure 1 From the XRD results, it can be seen that compared with the single transition metal catalyst of Comparative Example 1, the diffraction peak of the hexaaluminate in Comparative Example 3 is significantly enhanced. This may be because the doping of Co makes it easier for the metal to enter the hexaaluminate lattice to replace Al, which is more conducive to the generation of the hexaaluminate lattice. This may be the reason why the activity of Comparative Example 3 is better than that of Comparative Example 1. But at the same time, a small amount of diffraction peaks of metal oxides and perovskites appeared in Comparative Example 3, which shows that although the diffraction peak signal of the hexaaluminate has been enhanced, some metals still fail to enter the lattice well, while the diffraction peak of the hexaaluminate in Example 1 is sharper and has almost no impurity peaks. This may be due to the synergistic effect between Fe and Cu, and after N2O calcination, most of the metals enter the lattice, making the exposed crystal face of the hexaaluminate crystal phase easier to combine with N2O. Therefore, the diffraction peak of the hexaaluminate in Example 1 is stronger and the peak shape is smoother, which may be the reason why Example 1 has the best activity.
[0068] 3. H2-TPR characterization
[0069] The shaped catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 4 were characterized by H2-TPR. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the catalyst has H2 reduction peaks of CuO at around 200℃~400℃, among which the reduction peak at 200℃~300℃ is attributed to Cu 2+ Reduced to Cu + , the reduction peak at 300℃~400℃ is attributed to Cu + Reduced to Cu 0 According to the TPR results of Comparative Examples 1 and 4, after loading the oxide, the initial reduction peak shifted to the left, which may be the reason why Comparative Example 4 is more active than Comparative Example 1. Example 1 has the lowest reduction peak starting temperature and the largest reduction peak area, which may be the reason why Example 1 has the best activity.
[0070] It can be seen from the characterization test of the above catalyst that the redox ability of the catalyst can be effectively improved by loading oxides and calcining with N2O. When the doped transition metal is a bimetallic, the activity of the catalyst is further improved.
[0071] Catalyst performance test:
[0072] 0.1 g of each of the shaped catalysts prepared in Example 1 and Example 2 and Comparative Examples 1 to 4 was loaded into a quartz tube reactor, and gas components were introduced according to the composition in Table 2. At the same time, the temperature in the reactor was increased from 550°C to 850°C at a rate of 50°C / min. Under the reaction conditions in Table 1, an infrared spectrometer was used to monitor the outlet gas composition, and finally the catalyst activity data was obtained, as shown in Table 3.
[0073] Table 2 Catalyst performance evaluation reaction conditions
[0074] Catalyst mass (g) NO concentration (ppm) <![CDATA[N2O concentration (ppm)]]> <![CDATA[O2 content (%)]]> <![CDATA[Air speed (h -1 )]]> 0.1 700 2000 5 100000
[0075] Table 3 Catalyst activity evaluation results
[0076]
[0077] According to the results of catalyst activity evaluation in Table 3, it can be seen that the catalysts prepared in Examples 1 and 2 of the present invention have significantly improved activity compared to the catalysts prepared in Comparative Examples 1 to 4, and have strong stability. The conversion rate of decomposing N2O can always reach 100% when reacting continuously at 850°C for 10 hours, indicating that calcination under a loaded oxide and N2O atmosphere can improve the performance of the catalyst. The catalytic activity of Example 1 is further improved compared to Example 2, indicating that when the doped transition metal is a bimetallic, the performance of the catalyst is better due to the existence of synergistic effects. Therefore, the catalyst of the present invention has high catalytic activity and high temperature stability; at the same time, during the reaction process, the catalyst of the present invention will not decompose the original NO, but will also convert a portion of N2O into NO, thereby increasing the yield of nitric acid.
Claims
1. A method for preparing a hexaaluminate / oxide shaped catalyst for decomposing N2O in a nitric acid oxidation furnace, characterized in that: The following steps are involved: (1) preparing a nitrate solution with a pH of 1, adding a precipitant to the nitrate solution to obtain a coprecipitation reaction system, carrying out a coprecipitation reaction at 60 to 80° C. for 3 to 6 hours, washing with water, drying, and then calcining at 1100 to 1200° C. for 4 to 6 hours in a N2O atmosphere to obtain a hexaaluminate catalyst; (2) stirring a hexaaluminate catalyst, an oxide and water at 60 to 90° C. for 4 to 6 hours, rotary evaporating, and then calcining at 850 to 950° C. for 4 to 6 hours to obtain a hexaaluminate / oxide catalyst; (3) fully mixing the hexaaluminate / oxide catalyst, a binder, an extrusion aid, a peptizing agent and water to prepare a clay embryo, aging the clay embryo, extruding and molding it, drying it, and then calcining it at 850-950° C. for 4-6 hours to obtain a hexaaluminate / oxide molded catalyst; The oxide is one or two of aluminum oxide, zirconium oxide and silicon oxide.
2. The preparation method according to claim 1, characterized in that: The nitrate in step (1) is composed of nitrate of alkaline earth metal or rare earth metal, nitrate of transition metal and aluminum nitrate in a molar ratio of 1:1:
11.
3. The preparation method according to claim 2, characterized in that: The alkaline earth metal nitrate is at least one of barium nitrate and magnesium nitrate, the rare earth metal nitrate is lanthanum nitrate, and the transition metal nitrate is at least one of copper nitrate, iron nitrate and cobalt nitrate.
4. The preparation method according to claim 3, characterized in that: The precipitant in step (1) is a saturated ammonium carbonate solution, and the pH of the coprecipitation reaction system is 7 to 7.
5.
5. The preparation method according to claim 4, characterized in that: The amount of the oxide added in step (2) is 3.5 to 4.5 times the weight of the hexaaluminate catalyst.
6. The preparation method according to claim 5, characterized in that: The binder in step (3) is pseudo-boehmite, the extrusion aid is sesbania powder, and the peptizing agent is concentrated nitric acid.
7. The preparation method according to claim 6, characterized in that: In step (3), the mass ratio of the hexaaluminate / oxide catalyst, the binder, the extrusion aid and the peptizing agent is (40-70): (18-40): (4-10): (6-12).
8. The preparation method according to claim 1, characterized in that: The calcination heating rates of step (1), step (2) and step (3) are all 4°C / min.
9. A hexaaluminate / oxide shaped catalyst for N2O decomposition in a nitric acid oxidation furnace prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Hexaaluminate metal oxide catalyst, preparation methods and application thereof
CN102008954A
Three-stage reduction of N2O and NO X Method for producing nitric acid
CN111108063B
Catalyst and preparation and application thereof
CN101927160A
Preparation method of hexaaluminate catalysts with high specific surface areas
CN108097242A
Method and device for catalyzing decomposition of nitrous oxide
CN114832615A